ANALISIS PENGGUNAAN BANGUNAN PEREDAM BISING UNTUK MENGURANGI KEBISINGAN LALU LINTAS (STUDI KASUS JALAN ULUWATU II JIMBARAN) - Suastawa, I Wayan; Wedagama, D.M Priyantha; Suthanaya, IP. Alit (JURNAL SPEKTRAN; Vol. 3, No. 2, Juli 2015, 2015)
The present transport activities cause negative effects in the form of various kinds of diseases in the community. The government in this case, it makes use of the guidelines Noise Reduction Building (BPB) to reduce traffic noise. BPB in the design of Highways made ??of konblok ALWA (Artificial Low Weight aggregate) with a height of 2.75 meters was built along the road at a distance of 5 meters from the edge of the pavement. In this study, the noise level will be analyzed without and with unobstructed BPB. This study began from site selection studies, problem identification, goal setting research, development BPB, measuring noise levels without and with BPB analysis of the data and draw conclusions. From the analysis of the results obtained by calculation that the path chosen as the object of study, namely Jalan Uluwatu II Jimbaran without BPB has a noise value of 73.23 dB (A). While the values ??obtained BPB 61.85 decibels A, the value of this noise then most of the raw noise threshold has been exceeded so that some kind of designation of the area should be kept lying on the edge of the pavement. From the calculation of the distance from the edge of pavement to reduce noise levels in order to be secure appropriate noise threshold obtained for the allotment of residential, hospitals, schools and places of worship should be within 24.29 meters from the edge of the pavement. For government offices, public facilities should be located at a distance of 6.79 meters, while for offices, commerce, industry, services and stations could be placed as close as possible but still within the protection of BPB.
Keywords: Traffic Noise, Building Noise Reduction.